Islamic Government System: Between Abu Zahra and Ibn Taimiyya - Meirison, Meirison (Ijtihad, 2018)
Government based on Islamic law or the state or system of Islamic governance is a recipe for the life of the inherited state of Rasulullah S.A.W. An ideal government in Islam that has been done by friends. Therefore, it is important for Muslims to understand the structure of the Khilafah State that was carried out after the Prophet's time and then changed during the Umayyad period. There are two causes of the form of government in Islam, namely the Caliphate and the kingdom, both of which are considered legal. Abu Zahrah said that an Islamic state should be based on deliberation to appoint its leaders, or through representatives and leadership not inherited from generation to generation. whereas Ibn Taymiyyah is more flexible, he accepts the Kingdom system as long as the constitution of the Qur'an and Sunnah is absolute. Both of these practices of government have been traversed by Muslims for a long time, each of which has a privilege, both forms of government based on deliberation and descent are listed in the verses of the Qur'an.